In vitro Cultivation of Newly Reported Wild Edible Mushroom Volvariella bomybycina from Nepal - Chaudhary, Pradip Kumar; Shrestha, Mitesh; Poudel, Bal Hari; Adhikari, Mahesh Kumar (Nepal Journal of Biotechnology, 2017)
Wild edible mushrooms are becoming endangered all over the world. Very few wild edible mushrooms are found in natural habitat. Volvariella bombycina is an edible and medicinal mushroom. The mushroom was collected in natural habitat growing on Populus tree. Mycelium of the mushroom was developed in PDA slant tubes by tissue culture method, incubated at 25°C for 1-2 weeks. Spawn was developed in wheat grains after incubation at 25°C for 2-3 weeks. Substrates were formulated for the development of fruiting bodies by combination of paddy straw, saw dust and rice husk. Fruiting bodies of V. bombycina was cultivated in these substrates after incubation at 28 ± 2°C for 2-4 weeks. The work describes the optimized process for in vitro culture of wild edible mushroom Volvariella bomybycina.Nepal Journal of Biotechnology. Dec. 2017 Vol. 5, No. 1: 27-31